[Hillside View of Akureyri] - Streng, Evelyn Fiedler (1975)
Photograph of Akureyri from a hill. The city full of colorful buildings is visible past a line of white buildings in the foreground. Water is visible at the foot of green and snow covered mountains. The sky above is covered in grey clouds. A person in black and red takes a photograph in the bottom left corner of the photograph.